2022
DOI: 10.7759/cureus.33109
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax and Azacitidine in the Treatment of Blastic Plasmacytoid Dendritic Cell Neoplasm Refractory to Conventional Therapy

Abstract: Blastic plasmacytoid dendritic cell neoplasm is a rare and aggressive hematological malignancy associated with poor prognosis and limited treatment options. No guideline-directed therapy existed until the approval of tagraxofusp in 2018 by the Food and Drug Administration. Multiple clinical trials are undergoing as treatment options continue to evolve. We report a case refractory to tagraxofusp and pivekimab sunirine with subsequent remission achieved on venetoclax and azacitidine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In addition, tagraxofusp-resistant cells have been demonstrated to exhibit increased dependence on BCL2 ( 53 ). Although our findings did not show favorable responses to salvage treatment with Aza and/or Ven, these agents also hold promise for post-tagraxofusp relapse salvage treatment, as indicated by several case reports ( 36 , 40 , 41 ).…”
Section: Discussionmentioning
confidence: 44%
“…In addition, tagraxofusp-resistant cells have been demonstrated to exhibit increased dependence on BCL2 ( 53 ). Although our findings did not show favorable responses to salvage treatment with Aza and/or Ven, these agents also hold promise for post-tagraxofusp relapse salvage treatment, as indicated by several case reports ( 36 , 40 , 41 ).…”
Section: Discussionmentioning
confidence: 44%
“…In the present case, the patient presented with a TET2 mutation and was treated with the DNA methyltransferase inhibitor, azacytidine, in combination with venetoclax. Certain cases of BPDCN have been treated with azacitidine in combination with venetoclax and it was well tolerated (58,59). Moreover, azacitidine combined with tagraxofusp has been reported to be effective for BPDCN treatment, with azacitidine restoring sensitivity to tagraxofusp by restoring diphthamide biosynthesis protein 1 expression (60).…”
Section: Discussionmentioning
confidence: 99%
“…Gangat et al reported on five patients with primary BPDCN and five patients with relapsed BPDCN who received VEN-combined HMA therapy, in which VEN-combined HMA therapy led to CR in patients with BPDCN [5]. In addition, a previous case report described a patient with BPDCN who received continuous VEN/AZA therapy and remained in CR [6]. However, because patients treated with VEN/AZA therapy often present with FN, several patients, especially older adults or those who are unfit, discontinue VEN/AZA therapy [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that BPDCN cells target BCL2 proteins and are uniformly sensitive to VEN in vivo [4]. In addition, VEN-combined chemotherapy is reportedly effective in patients with primary and relapsed BPDCN [5,6].…”
Section: Introductionmentioning
confidence: 99%